Invasive pulmonary aspergillosis - Andrade, Luís (2009)
Aspergillosis is caused by a fungus of the genus Aspergillus, which is present in the environment. Although human colonization is frequent, disease due to tissue invasion is uncommon and occurs primarily in the setting of immuno-suppression. In the majority of cases the prognosis is bad, given the epidemiological characteristics of the affected population and the pathogenesis of this fungus. Early diagnosis and management is therefore essential to control infection and has repercussions on the prognosis.